Blueprint of political reforms - Kashyap, Subhash C.; Centre for Policy Research (New Delhi, India) (Delhi : Shipra Publications, 2003)
In the Indian context.
"Under the auspices of Centre for Policy Research, New Delhi."
Includes index.
BIGD
Keywords: Public administration -- India; Constitutional history -- India; India -- Politics and government -- 1947-